Students’ Difficulties in Answering the TOEFL Listening Test - Ulminarika Ulminarika (English LAnguage Study and TEaching, 2023)
The aim of this study was to know the difficulties faced by students in answering the TOEFL listening test at the English Department of the University of Serambi Mekkah, Banda Aceh The research design used in this study was a descriptive quantitative study. The participants of this study were 25 students who have taken the TOEFL preparation course. In collecting the data, the author distributed a questionnaire, and all the obtained data were analyzed using the percentage formula. The result of the study showed that the student’s difficulties in answering the TOEFL, especially in the listening section are mainly caused by four factors as follows: (1) conversational implicature factor, (2) idiomatic expression factor, (3) lack of vocabulary factor, and (4) lack of practice factor. The most important factor was the first factor or conversational implicatures, which is 76%. Based on the conclusions above, the writer offers some recommendations with regard to the results of the study. Since the implicature factors seem one of the difficult factors for the students in answering the listening section of TOEFL thus the lecturers should encourage students to pay more attention to implicature factors.